COMPARATIVE STUDY OF STATIC METRICS OF PROCEDURAL AND OBJECT ORIENTED PROGRAMMING LANGUAGES - Sharma, Manik; Sharma, Chandni; Bhardwaj, Ankur; Singh, Navpreet; Singh, Lakhbir (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The goal of this study is to compute and analyze an assortmentof static software metrics for different programming methods ortechniques. Software engineering is branch of Computer Sciencethat deals with an effective development and analysis ofsoftware product. Software engineering provides the concept ofmetrics with the help of which the complete investigation ofcode can be done in static or in dynamic way. The staticmetrics helps in measuring the effectiveness of code withoutexecuting the actual program. In this study the focus is given onanalyzing the different programming methods like function,constructor, overloading and virtual functions.